The Effect of Financial Literacy and Entrepreneurial Competence on The Performance of Micro, Small and Medium Enterprises (MSMES) - Sari, Rahayu Permata; Sudarma, Ade; Suherman, Acep (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the influence of financial literacy and entrepreneurial competence on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Sukaraja Market, Sukabumi Regency. The approach used is quantitative with descriptive and verifiable methods. The sample in this study amounted to 187 respondents who were selected using the purposive sampling technique. Data collection was carried out through questionnaires and interviews, while the data analysis technique used multiple linear regression preceded by tests of validity, reliability, and classical assumptions. The results of the study show that financial literacy has a positive and significant effect on the performance of MSMEs. This means that the higher the understanding of business actors in managing finances, the better their business performance. In addition, entrepreneurial competence also has a positive and significant effect on the performance of MSMEs, which reflects the importance of innovation, managerial, and decision-making skills in supporting business success. Simultaneously, these two variables explain 65% variation in MSME performance. These findings confirm that increasing financial literacy and entrepreneurial competence is a strategic factor in strengthening the competitiveness and sustainability of local MSMEs. This research provides practical implications for policymakers and business actors in designing MSME empowerment programs.